Functional Inactivation and Appearance of Breaks in RNA Chains Caused by Gamma Irradiation of Escherichia coli Ribosomes - Kućan, Željko (1971)
70S ribosomes and 30S ribosomal subunits from Escherichia coli MRE 600 were exposed to gamma irradiation at -80szC. Exponential decline of activity with dose was observed when the ability of ribosomes to support the synthesis of polyphenylalanine was assayed. Irradiated ribosomes showed also an increased thermal lability. D(37) values of 2.2 MR and 4.8 MR, corresponding to radiation-sensitive molecular weights of 3.1 × 10(5) and 1.4 × 10(5), were determined for inactivation of 70S ribosomes and 30S subunits, respectively. Zone sedimentation analysis of RNA isolated from irradiated bacteria or 30S ribosomal subunits showed that at average, one chain scission occurs per four hits into ribosomal RNA. From these results it was concluded that the integrity of only a part of ribosomal proteins (the sum of their molecular weights not exceeding 1.4 × 10(5)) could be essential for the function of the 30S subunit in the polymerization of phenylalanine. This amount is smaller if the breaks in the RNA chain inactivate the ribosome.